Challenges Facing Persons with Physical and Visual Disabilities in Accessing Housing Needs; A Case Study of Bungoma Municipality - Mukoche, Wamalwa Chrispinus W; Kisilu, Kitainge; Catherine , Sempele (Nurture, 2014)
Persons with disabilities constitute 3.5% of the total population in Kenya. According to the 2009 census, there are approximately 1,330,312 persons with disabilities in Kenya. The disabilities range from visual, audio, physical and intellectual challenges. The study focused on the physical and visual challenges. These persons face discrimination due to socio-cultural and economic factors. Persons with physical and visual disabilities have unique housing needs due to the nature and degree of their disability. It is therefore important that housing design and construction take these unique consumer needs of persons with physical and visual disabilities into consideration. The paper examines the findings of the study that investigated the challenges persons with physical and visual disabilities face in accessing decent and affordable housing in informal and low income settlements within Bungoma Municipality. A sample survey design was employed where interviews, observation checklists and field participatory methods were used. Guided sampling technique was used in identifying research participants or respondents, while a snowballing technique was employed to identify respondents with physical and visual disabilities. The findings showed lack of water borne sanitary facilities in informal and low income settlements in urban areas. The roads and pathways were found to be muddy and narrow to accommodate the needs of persons with disabilities. The sewage and drainage systems were poor and posed great risks to persons with disabilities. The land lords/ladies were found ignorant about the needs for persons with disabilities. The paper concludes that physically and visually challenged persons face numerous challenges in accessing decent and affordable housing in informal and low income settlements. The paper recommends rigorous implementation of Persons with Disabilities Act (2003) and that the persons with disabilities themselves to intensify advocacy and awareness, raising programs that will make housing for persons with disabilities, human rights and development agenda.